Pengaruh Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Pada Kopi Nako Waisata Cibubur - Nico Sharon Purba; Asep Maulana (LPPM Universitas Buddhi Dharma, 2024)
Study This aim For know , and analyze How influence in a way Partial price to decision purchase consumers ( Case study of Caffe Kopi Nako Kota Wisata Cibubur ). For know and analyze How influence in a way Partial quality product to decision purchase consumers ( Case study of Caffe Kopi Nako Kota Wisata Cibubur ), for know and analyze in a way simultaneous between variable price and quality product to decision purchase consumers ( Case study of Caffe Kopi Nako Kota Wisata Cibubur ). Research methods used in study This that is use method quantitative. As for population from study This is ever consumer visit to Caffe Kopi Nako Kota Wisata Cibubur. With a sample of 100 respondents range aged 15 to 25 years chosen use technique taking random sampling using stratified random sampling is sampling method set group from level certain.analyzed with tools help spss 25.0. Analysis techniques used in study here that is use analysis multiple linear regression with hypothesis testing in a way partial and simultaneous.Based on results analysis pointed out that there is influence price to decision purchase consumers of Nako coffee , there are influence quality product to decision purchase consumers on Nako coffee . By together price and quality product own influence in a way simultaneous to decision Purchases at Nako Coffee.